(3MhGTj GdTQja GdLQLGfj Ydi TQM GdQVi Ydi GdcGajIs - (3Ydj Hf eMeO Hf Ydj, GdeYQha HGdTQja GdLQLGfj,J (B816 (3g` s; (3GdQVj eMeO Hf GdMSf GdGSJQGHGPj,J (B686 (3g` s
(3ChdgG (B:s
(3JGgJ aj ahGaj(B: (3GdahGaj GdeaGhR, LeY ahaGI, hCUdgG ahahI Ydi aYddI, hgj eVGYa bdHJ hGhgG CdakG s
(3BNQgG (B:s
(3bhdg(B: (3CTGgQf(B: (3TgQ Sjag Cj Sdg bhdg(B: (3hGdfhf GdNajaI hCeG Gdfhf GdSGcfI aJMPa ddSGcfjf Je s
(3GdcGajI dCHhYeQh LeGd GdOjf YKeGf GHf GdMGLH GdeJhai (B646(3g``s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B86 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B183s
Keywords: (3GdfMhs